PERAN ACTIVITY BASED MANAGEMENT DALAM MENINGKATKAN EFISIENSI PADA MOOVBY INDONESIA - Nofa Sri Lestari; Suyanto Suyanto; Angga Kurniawan (Jurnal Akuntansi AKTIVA, 2021)
This study aims to help managing the activities of the company in increasing efficiency. To find out whether the company still has non-value-added activities by using the activity-based management method to reduce the waste that occurs. Cost efficiency is an important strategy for companies in maintaining their business. This research is qualitative in nature with the type of case study research on the vehicle rental service company Moovby Indonesia. From the analysis carried out, there are four non-value-added activities at Moovby Indonesia, namely pickup and delivery of late vehicles, vehicle damage, installation of GPS-tracker and bank admin fees.